An S-shaped double helicene showing both multi-resonance thermally activated delayed fluorescence and circularly polarized luminescence. Issue 12 (3rd February 2022) - dos Santos, John Marques; Sun, Dianming; Moreno-Naranjo, Juan Manuel; Hall, David; Zinna, Francesco; Ryan, Seán T. J.; Shi, Wenda; Matulaitis, Tomas; Cordes, David B.; Slawin, Alexandra M. Z.; Beljonne, David; Warriner, Stuart L.; et al.
Abstract : We present the first example of a MR-TADF extended helicene. Abstract : We present the first example of a multi-resonant thermally activated delayed fluorescent (MR-TADF) extended helicene, Hel-DiDiKTa . This S-shaped double helicene exhibits sky-blue emission, a singlet–triplet energy gap, Δ E ST, of 0.15 eV and narrow emission at a peak maximum of 473 nm with a full-width at half-maximum of 44 nm in toluene. The MR-TADF character is confirmed by the small degree of positive solvatochromism and temperature-dependent increase in intensity of the delayed emission. The chiroptical properties of the separated enantiomers are similar to other large helicenes with comparable dissymmetry values, but with the added benefit of MR-TADF. ( P )-Hel-DiDiKTa is stable towards enantiomerization, with a Gibbs free energy of activation for enantiomerization (Δ G ‡e) of 31 ± 2 kcal mol −1 at 298 K, a value similar to other reported double helicenes. ( P )-Hel-DiDiKTa is also thermally stable, with a 5% weight loss at 399 °C revealed by thermogravimetric analysis (TGA). Thus, this study further strengthens the burgeoning area of chiral TADF emitters for use in cutting-edge optoelectronic and photocatalytic molecules and materials.